A New Model for Adult Literacy Education: Technology-Based Concept Mapping in GED Preparation - Larry G. Martin (Adult Education Research Conference, 2014)
This paper explores the potential for the effective integration of concept mapping into the teaching of GED preparation programs in ways that benefit the academic achievement of learners through the implementation of a New Model of literacy education.